An intelligent system for tribological design in engines - Zhang, Xiangjun; Gui, Changlin; ScienceDirect eBooks (Amsterdam ; San Diego, Calif. : Elsevier, 2004)
The internal combustion is widely used as a power source in engineering. As the demands placed upon engines have increased, tribology has come to play an increasingly important role in their development. This book is a creative combination of intelligent design technology and the tribological design of engines: engine tribology, information science, artificial intelligence, non numerical algorithms, modern design technology and dynamics to propose new methodology and technology for tribological engine design. It not only presents an effective approach to l engine design but also explores a new pattern for research and l design methodology. An essential reference for the design of more effective and efficient engines Proposes new techniques for tribological engine design Combines advanced design technologies with traditional tribological design methods.
Chapter 1. Engine Tribological Design Methodology and Intelligent System; Chapter 2. General consideration of Tribological design of an engine; Chapter 3. A Symbol Model-based Intelligent System and its Implementation; Chapter 4. The Artificial Neural Network Model and its Application in ICADEDT; Chapter 5. Gene Model-based Comprehensive Decisions for Tribological Design; Chapter 6 A Hierarchical Cooperative Evolutionary Design for Engines; Appendix A; Subject Index.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Elsevier
Keywords: Tribology; Engines -- Design and construction; Engines -- Lubrication; Machine design; TECHNOLOGY & ENGINEERING -- Tribology; Engines -- Design and construction; Machine design; Tribology; Electronic books